Однофазные источники напряжения и мощности с релейным управлением - Самчелеев, Юрий Павлович; Белоха, Галина Сергеевна (Национальный технический университет "Харьковский политехнический институт", 2019)
Показана возможность построения на базе источников тока однофазных источников питания, состоящих из активного выпрямителя и реверсора, с релейным управлением, реализующих режим источников напряжения и мощности электромагнитно-совместимых с сетью и малой чувствительностью к действию возмущений. Получены математические модели, описывающие процессы в источниках питания и структурные схемы, а также выражения для определения частот релейного режима.

The article presents the possibility of building on the basis of current sources single-phase power sources, consisting of an active rectifier and reverser, with relay control, realizing the mode of voltage and power sources electromagnetically compatible with the network and low sensitivity to disturbances, limiting speed in working out the driving and disturbinginfluences: changes in network voltage and increase in load resistance. Mathematical models describing the processes in power supplies and structural diagrams, as well as expressions for determining the relay mode frequencies, are obtained. The possibility of converting the AC mains voltage into a single-phase AC voltage of various shapes and adjustable frequency and amplitude is shown. The spectrum of phase currents is presented. THD values do not exceed the limits specified by the standard. The possibility of building a universal power source that implements the modes of the current source, voltage and power is shown. The required mode of operation is performed by selecting the type of feedback.
Single-phase voltage and power sources with relay control
Keywords: электромагнитная совместимость; electromagnetic compatibility